Optimalisasi Pengelolaan Sampah Di Tempat Pemrosesan Akhir (TPA) Rawa Kucing Kota Tangerang (Dari Perspektif Komunikasi dan Sumber Daya Penanggulangan Sampah) - Siti Alvina Maulidah; Isniyunisyafna Diah Delima; Muhammad Ibrahim Rantau (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
Various problems that are currently happening at the Rawa Kucing TPA are that the volume of waste increases every year. The Tangerang City Government issued Regional Regulation Number 2 of 2022 concerning Tangerang City Waste Management as an effort to overcome this problem. This study aims to discuss the Optimization of Waste Management at the Rawa Kucing Final Processing Site (TPA) in Tangerang City (Viewed from Communication Resources and Waste Management). Researchers used a type of qualitative descriptive research that refers to data collection techniques used through observation, interviews, and documentation. Researchers use the theory of Van Meter Van Horn Policy Implementation. The results of the study show that policy sources are not supportive in carrying out waste management so that the waste problem in Tangerang City, especially at the Rawa Kucing TPA, has not been handled optimally. the quality of human resources at Rawa Kucing TPA in terms of minimal education, the budget has not been fulfilled in overcoming waste problems at Rawa Kucing TPA, one of which is the PLTSa program, and in terms of equipment it is still lacking. It is necessary to carry out waste management at the Rawa Kucing TPA, besides that communication between stakeholders is good, but there are still obstacles in external communication as indicated by the low awareness of the community to dispose of waste in its place, and many people who do not know about the policies and existence of PERDA in waste management. To achieve the goals of the waste management policy at Rawa Kucing TPA, cooperation and participation of the target group is needed, namely the community so that the policies made by the government can work and achieve the desired goals.